2006
DOI: 10.1097/01.shk.0000217815.57727.29
|View full text |Cite
|
Sign up to set email alerts
|

Tlr2, Tlr4, Cd14, Cd11b, and Cd11c Expressions on Monocytes Surface and Cytokine Production in Patients With Sepsis, Severe Sepsis, and Septic Shock

Abstract: Bacterial recognition and induced cellular activation are fundamental for the host control of infection, yet the limit between protective and harmful response is still inexact. Forty-one patients were enrolled in this study: 14 with sepsis, 12 with severe sepsis, and 15 with septic shock. Seventeen healthy volunteers (HV) were included as control. The expression of TLR2, TLR4, CD14, CD11b, and CD11c was analyzed on monocytes surface in whole blood. sCD14 was measured in serum, and TNF-alpha, IL-6, and IL-10 cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
79
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 34 publications
14
79
3
1
Order By: Relevance
“…Superantigens have been shown to upregulate the expression of both TLR2 and TLR4 on isolated human monocytes (6,7,26), which was also observed in the current study (data not shown). Although this upregulation by superantigen of TLRs may play a role in the increased responsiveness of the innate immune system in superantigen-mediated septic shock, other research has shown that in patients with severe sepsis, TLR expression does not correlate well with ligand sensitivity (31,32). We therefore analyzed the effect of superantigens on other aspects of the TLR-mediated intracellular signal transduction pathway.…”
Section: Discussionmentioning
confidence: 96%
“…Superantigens have been shown to upregulate the expression of both TLR2 and TLR4 on isolated human monocytes (6,7,26), which was also observed in the current study (data not shown). Although this upregulation by superantigen of TLRs may play a role in the increased responsiveness of the innate immune system in superantigen-mediated septic shock, other research has shown that in patients with severe sepsis, TLR expression does not correlate well with ligand sensitivity (31,32). We therefore analyzed the effect of superantigens on other aspects of the TLR-mediated intracellular signal transduction pathway.…”
Section: Discussionmentioning
confidence: 96%
“…Increased expression of TLR2 by EC in response to inflammatory mediators such as TNF, LPS, IL-1β, IFNγ and histamine in vivo and in vitro [49][50][51][52], however, provides a mechanism allowing EC to respond to TLR2 ligands under inflammatory conditions. TLR2 and TLR4 are both expressed on platelets [53] and on monocytes [54]. Sorice et al [55] have identified that TLR4, β2GP1 and annexin A2 form an activation cluster in plasma membrane microdomains of human monocytes after LPS or aPLA ligation.…”
Section: The Role Of Members Of the Tlr Familymentioning
confidence: 99%
“…THP1 cells (1 3 10 6 ) after different treatments were harvested and washed twice with PBS. For detection of surface markers, cells were resuspended in Ca 2+ -Mg 2+ HBSS and incubated with conjugated primary Abs (TLR2-rPE, TLR4-FITC, CD11b-rPE, and CD36-FITC) for 30 min in the dark at 37˚C as described earlier (26,27). After labeling, cells were washed with PBS and resuspended in 1 ml Ca 2+ -Mg 2+ HBSS, and 10,000 events were analyzed by FACS.…”
Section: Flow Cytometrymentioning
confidence: 99%